The musculature that drives active touch by vibrissae and nose in mice - Haidarliu, Sebastian (Anat Rec (Hoboken), 2014)
Coordinated action of facial muscles during whisking, sniffing and touching objects is an important component of active sensing in rodents. Accumulating evidence suggests that the anatomical schemes that underlie active sensing are similar across the majority of whisking rodents. Intriguingly, however, muscle architecture in the mystacial pad (MP) of the mouse was reported to be different, possessing only one extrinsic vibrissa protracting muscle (M. nasalis) in the rostral part of the snout. In the present study, the organization of the muscles that move the nose and the mystacial vibrissae in mice was re-examined and compared with that reported previously in other rodents. We found that muscle distribution within the MP and around the tip of the nose in mice is isomorphic to that found in other whisking rodents. In particular, in the rostral part of the mouse snout, we describe both protractors and retractors of the vibrissae. Nose movements are controlled by the M. dilator nasi and five subunits of the M. nasolabialis profundus, with involvement of the nasal cartilaginous skeleton as a mediator in the muscular effort translation.